Polyvinylpyrrolidone/polyaniline composite based 36° YX LiTaO3 surface acoustic wave H2 gas sensor - Amir Sidek,; Rashidah Arsat,; Xiuli He,; Kourosh Kalantar-Zadeh,; Wojtek Wlodarski, (Universiti Kebangsaan Malaysia, 2013)
Poly-vinyl-pyrrolidone (PVP)/polyaniline based surface acoustic wave (SAW) sensors were fabricated and characterized and their performances towards hydrogen gas were investigated. The PVP/polyaniline fibers composite were prepared by electrospinning of the composite aqueous solution deposited directly onto the active area of SAW transducers. Via scanning electron microscopy (SEM), the morphology of the deposited nanostructure material was observed. From the dynamic response, frequency shifts of 6.243 kHz (1% H2) and 8.051 kHz (1%were recorded for the sensors deposited with PVP/ES and PVP/EB, respectively.